Pengalaman Ibu Usia Remaja Dalam Pemberian ASI Eksklusif: THE EXPERIENCE OF TEENAGE MOTHER IN PROVIDING THE EXCLUSIVE BREASTFEEDING - Nurjanah, Suci; Waliulu, Syariefah Hidayati; Rumata, Jihan Priyani (WELL BEING, 2023)
ABSTRACT Decision to give breastfeeding in teenage mothers is a dilemma, the mother must meet the developmental task of adolescence and need to perform the role as parents. This study aim to more identify the experience of teenage mother in providing the exclusive briestfeeding. This study has used qualitative method to get more information by deep interview. Participants in this study were teenage mothers aged 19 years old and had 6 babies aged 0 to 24 months old. The results of this research showed that teenage mothers decided to continue breastfeeding because they realized the good benefits, namely, making the baby's growth and development faster, healthier and stronger. Breastfeeding is more practical and increases the mother's appetite and saves the economy. Teenage mothers experience painful physical experiences such as pain, swelling, tenderness, sores on the breasts and weight loss. Feelings of pleasure arise in teenage mothers because of breastfeeding a baby. The teenage mother who have stopped breastfeeding because the baby has been fed and one of the others is because of breastfeeding problems. Teenage mother receive support from both their families and cadres in the form of support to continue breastfeeding, motivation and counselling. Keywords: Teenage mother, Exclusive breastfeeding